2010
DOI: 10.1111/j.1743-6109.2009.01561.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Sexuality—Does it Really Matter?

Abstract: Introduction The extent to which diabetes may influence sexuality has not yet been established. Identifying the risk factors of female sexual dysfunctions will facilitate the introduction of effective therapeutic models that aim to normalize the glycemic control and will enhance sexual functioning. Aims To evaluate the influence of diabetes mellitus on female sexual functions, behaviors and depressive symptoms as well as to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 52 publications
(216 reference statements)
9
53
4
Order By: Relevance
“…Only 9 studies looked specifically at MS [2,25,26,27,28,29,30,31,32]. The remaining included data about components of MS [2,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 9 studies looked specifically at MS [2,25,26,27,28,29,30,31,32]. The remaining included data about components of MS [2,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. …”
Section: Resultsmentioning
confidence: 99%
“…Total 35 studies met the inclusion criteria (Table 1, 2) [2,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. Sixteen studies were classified as case-control studies [2,28,29,32,37,38,39,41,42,44,47,49,51,52,54,57] and the rest as observational/cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…42,49,50 in several ethnic groups (US, Italian, Polish, Turkish, Iranian, Jordanian, Nigerian, Peruvian populations) have reported a high prevalence of sexual dysfunction in women with either type 1 or type 2 diabetes. [40][41][42][43][44][45][46][47][48][49][50][51][52][53] These data are important since various cultures, religions, lifestyle habits and sexual behaviours are considered. Although the prevalence varies (Table 1) 40,42-53 depending on the criteria used to define sexual dysfunction in each study, it appears that sexual dysfunction is slightly lower in women compared to men, 13,54,55 it is twice that of the population without diabetes, 13,40,45,48,56 and it includes all the domains of sexual dysfunction.…”
Section: Diabetes Mellitus and Female Sexual Dysfunctionmentioning
confidence: 99%
“…[43][44][45]47,51,52 The incidence of arousal problems in women with diabetes is also variable, depending on the type of diabetes and the definition of arousal, and varies from 14 to 76% to no effect at all. [42][43][44][45][46][47]49,51,52 Regarding orgasm, most studies have indicated problems in women with diabetes ranging from 10-84%, [43][44][45][46]49 with a few studies showing no effect. 56 Finally, the risk of dyspareunia in women with diabetes varies from zero to 43%, with the higher prevalence being observed in type 2 diabetes.…”
Section: Diabetes Mellitus and Female Sexual Dysfunctionmentioning
confidence: 99%
“…24 According to the results of this study, female patients with type II diabetes had low levels of sexual function that was consistent with results of other studies done by Basok 25 and Nowosieslski. 26 Diabetes adversely affects women's sexual activities by causing neurological, hormonal and psycho-social disorders. Diabetes changes levels of androgen, estrogen and sex hormone-binding globulin and adversely affects women's sexual functioning.…”
Section: Original Articlementioning
confidence: 99%